Structure of Phytoplankton Community In Sungaitohor Kepulauan Meranti District, Riau Province - Yanasari, Nurry; Samiaji, Joko; Siregar, Sofyan Husein (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in October 2016 until January 2017 by using survey method. The purpose of this research was to determine the water quality, the structure of phytoplankton community and the relationship between the water quality with the abundance of phytoplankton in Sungaitohor Estuary Kepulauan Meranti District, Riau Province. Identification and analysis of phytoplankton was conducted at Marine Biology Laboratory Faculty of Fisheries and Marine University of Riau. The correlation regression analysis showed that the relationship between pH and phytoplankton abundance were very low, meanwhile correlation regression analysis between salinity and phytoplankton abundance was fair. The abundance of phytoplankton ranged between 25 - 75 ind/l, diversity index (H ') ranged from 0,81 – 1,89 (medium category), uniformity index (E) ranged from 0,12 – 0,30 (low category) and dominance index (C) ranged from 0,29 – 0,67 (medium category). The identification found 11 genera of phytoplankton i.e. : Leptocylindrus, Protoperidinium, Trichodesmium, Isthmia, Gonyaulax, Nitzschia, Cestum, Skeletonema, Thalassiosira, Stephanopyxis and Streptotheca. Protoperidinium was found in each stations.Keywords : Phytoplankton, Community Structure, Sungaitohor.